Toward the excited meson spectrum of dynamical QCD - PEARDON, MICHAEL; THOMAS, CHRISTOPHER (My University, 2010)
We present a detailed description of the extraction of the highly excited isovector meson spectrum on dynamical anisotropic lattices using a new quark-field construction algorithm and a large variational basis of operators. With careful operator construction, the combination of these techniques is used to identify the continuum spin of extracted states reliably, overcoming the reduced rotational symmetry of the cubic lattice. Excited states, states with exotic quantum numbers (0+-, 1-+ and 2+-), and states of high spin are resolved, including, for the first time in a lattice QCD calculation, spin-four states. The determinations of the spectrum of isovector mesons and kaons are performed on dynamical lattices with two volumes and with pion masses down to ~400??MeV, with statistical precision typically at or below 1% even for highly excited states.
PUBLISHED
Keywords: High Energy Physics; Phenomenology